Study of antinociceptive activity of SSRI (fluoxetine and escitalopram) and atypical antidepressants (venlafaxine and mirtazepine) and their interaction with morphine and naloxone in mice - Pranav Sikka; Sadhna Kaushik; Gyanendra Kumar; Seema Kapoor; V K Bindra; K K Saxena (Wolters Kluwer Medknow Publications, 2011)
Objective : to study the probable site of antinociceptive action of SSRI (fluoxetine, escitalopram) and atypical antidepressants (mirtazapine, venlafaxine) and their interaction with morphine and naloxone. Materials and Methods : the study was conducted on albino mice (25-35 grams) of either sex. Different doses of morphine (0.5 and 1 mg/kg), fluoxetine (2, 5 and 10 mg/kg), venlafaxine (30, 40 and 50 mg/kg), mirtazapine (3, 5 and 7 mg/kg) and escitalopram (2.5, 5 and 10 mg/kg) were administered subcutaneously to obtain their subanalgesic doses using tail flick analgesiometer. Tail flick latencies were obtained at 15, 30, 60 and 120 min. after drug administration. Naloxone (1 mg/kg) was administered 10 minutes prior to test drug for testing antagonism. Observations : fluoxetine (5 and 10 mg/kg), mirtazapine (5 and 7 mg/kg) and venlafaxine (40 and 50 mg/kg) were found to have antinociceptive activity but not at lower doses. Escitalopram failed to show any antinociceptive activity at any of the doses used. The antinociceptive effect of all the drugs was antagonized by naloxone (1 mg/kg). Further, subanalgesic doses of fluoxetine, mirtazapine and venlafaxine showed analgesic activity with suboptimal dose of morphine (0.5 mg/kg). Result and conclusion : fluoxetine, mirtazapine and venlafaxine have antinociceptive activity whereas escitalopram doesn't; their site of action seems to be the same as that of opioid analgesics ('mue' receptors). However, other pathways (cholinergic, histaminic, noradrenergic, GABAergic) may be involved in mediation of their analgesic activity, deserving further elucidation. Results apparently show that these drugs may be useful in the management of pain as monotherapy or in combination with other opioids.